2023
DOI: 10.1097/mcp.0000000000001007
|View full text |Cite
|
Sign up to set email alerts
|

Co-morbid insomnia and sleep apnea (COMISA): recent research and future directions

Alexander Sweetman,
Amal Osman,
Leon Lack
et al.

Abstract: Purpose of review Insomnia and obstructive sleep apnea have previously been viewed as completely independent conditions. However, there is now increasing recognition that insomnia and sleep apnea frequently co-occur. Co-morbid insomnia and sleep apnea (COMISA) is a highly prevalent condition that is associated with impairment of sleep, daytime function, mental health and physical health outcomes, and mortality risk. This review aims to provide an update on COMISA prevalence, consequences, treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Although CPAP therapy improves stability of the upper airway during sleep and many of the associated consequences of OSA, it is limited by suboptimal acceptance and long-term use for the duration of the sleep period (Weaver and Grunstein, 2008). Co-morbid insomnia symptoms are associated with approximately a 30% reduction in initial acceptance of CPAP therapy, and a 2-h reduction in average nightly CPAP use compared to patients with OSA alone (Sweetman et al, 2023b). Two of four recent randomized controlled trials have reported that CBTi improves subsequent acceptance and use of CPAP therapy in patients with COMISA (Bjorvatn et al, 2018;Sweetman et al, 2019b;Ong et al, 2020b;Alessi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although CPAP therapy improves stability of the upper airway during sleep and many of the associated consequences of OSA, it is limited by suboptimal acceptance and long-term use for the duration of the sleep period (Weaver and Grunstein, 2008). Co-morbid insomnia symptoms are associated with approximately a 30% reduction in initial acceptance of CPAP therapy, and a 2-h reduction in average nightly CPAP use compared to patients with OSA alone (Sweetman et al, 2023b). Two of four recent randomized controlled trials have reported that CBTi improves subsequent acceptance and use of CPAP therapy in patients with COMISA (Bjorvatn et al, 2018;Sweetman et al, 2019b;Ong et al, 2020b;Alessi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%